The influence of strong carbide-forming elements and homogenization on the wear resistance of ferritic stainless steel - Aksoy, M; Kuzucu, V; Korkut, MH (Elsevier Science Sa, 1997)
The influence of strong carbide-forming elements such as Mo, Ti, V and Nb, and homogenization on the abrasive wear resistance, surface hardness, microhardness and toughness of ferritic stainless steels containing 18 wt.% Cr was investigated. It was seen that these elements increased the microhardness and wear resistance, but decreased the surface hardness. However, they did not affect the toughness considerably. The homogenization increased the wear resistance, microhardness and toughness. It also increased the surface hardness of the other samples except for the sample which did not contain these elements. It was concluded that, for applications where corrosion is not important, the existence of some M23C6 carbides together with MC carbides in the microstructure is useful for wear resistance. (C) 1997 Elsevier Science S.A.
Keywords: stainless steel; microstructure; carbides; abrasive wear; hardness; toughness